From Translation to Transcreation in the Tourism Industry: SMEs and the Arab Market - Saleh Hussein, Hanan (Estudios de Traducción, 2020)
This study aims to outline a translation analysis of the websites of Spanish hotel companies operating internationally, specifically in Arab countries, in order to detect the most appropriate translation strategies when it comes to translating cultural aspects from Spanish to Arabic and which may contribute to the successful expansion of SMEs. Another aim is to develop new requirements in the specialisation of software translation in the Spanish-Arabic combination, based on the business translation model and using a cultural approach that seeks increased marketing success for SMEs in the Spanish hotel market.
Keywords: Specialised translation; transcreation; Arabic language; internationalisation; SMEs